Global burden of tuberculosis attributable to diet low in whole grains from 1990 to 2021, with projection to 2045 - Lu, Xiaoning; Lu, Xiaowei; Jiang, Miaomiao; Liu, Xiang (Frontiers in Nutrition, 2025)
BackgroundThis study, based on data from the Global Burden of Disease Study 2021 (GBD 2021), aims to analyze the global, regional, and national burden of tuberculosis attributable to diet low in whole grains (TB-DLWG) from 1990 to 2021, and to project trends through 2045.MethodsUsing GBD 2021 data, the study assessed the burden of TB-DLWG through disability-adjusted life years (DALYs) and mortality rates. Decomposition analysis, cross-national inequality analysis, and the Nordpred model were employed to evaluate historical trends and predict future patterns.ResultsIn 2021, TB-DLWG accounted for 177,303.55 DALYs globally, representing an 8% decrease from 1990. The number of deaths was 5,539.13, a 12% reduction. However, the burden increased in low Socio-demographic Index (SDI) regions, particularly in Southern Sub-Saharan Africa. Cross-country inequality analysis revealed that low-SDI countries bore a heavier burden, though relative inequality showed improvement. Projections indicate that by 2045, the absolute number of DALYs and deaths may increase globally, but age-standardized DALY rates (ASDR) and age-standardized mortality rates (ASMR) are expected to gradually decline and stabilize.ConclusionAlthough the global burden of TB-DLWG has generally declined, low SDI regions still face significant challenges. There is an urgent need to enhance public health resource allocation, promote whole grain consumption in low SDI regions.